THE STUDENTS’ PERCEPTION ON THE USE OF DICTOGLOSS STRATEGY IN TEACHING - Amaral Gibran; Nur Qalby (English Language Teaching Methodology, 2021)
This study aims to find out (1) the students' perception; (2) The result of this research can help the teacher to more comfortably present the material about Dictogloss strategy, (3) The result of this research can be used as a reference to improve the ability of the student in understanding more about Dictoglos Strategy. This study uses a descriptive quantitative approach and data collection questionnaire. The result findings found that on two types of students' perceptions. The first type is students' positive perception, and the second types are students' negative perception on the use of Dictogloss strategy in teaching listening. At point 1 which was positive, namely, I feel motivated to do my English task on Dictogloss Strategy, this was evidenced by the large students’ response showing that 16 (61.53%) out of the students choose to Agree, and 9 (34.61%) choose Strongly Agree. Meanwhile, at point 14, students prefer to ask classmates about something they don't know then ask the teacher. The question is negative so that many students disagree with the question, the response showing that 14 (53.84%) out of the students choose strongly disagree, and 6 (23.07%) choose to disagree. The fact is that students prefer to ask the teacher to ask their classmates. Dictogloss strategy most of the students gave a positive response in teaching listening.